124k views
3 votes
Rewrite the equation in Ax+By=C form. Use integers for A, B, and C.

Rewrite the equation in Ax+By=C form. Use integers for A, B, and C.-example-1
User MarGin
by
5.2k points

1 Answer

5 votes

Answer:

Explanation:

move things to the other side of the equal sign as you need to and change their sign

(-1/6)x -y = 2

A= -1/6

B= -1

C= 2

User Harkirat Saluja
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.